Empowering MSMEs in the Creative Economy of the Agrobusiness Industrial Sector in the Baranangsiang Area,BogorCity,West Java. - IGP Ratih Andaningsih; Prihandono; Andi Heru Susanto (Cita Konsultindo Research Center, 2022)
The author in conducting this study wanted to find out how far the empowerment of MSMEs in the creative economy in improving the MSME agro industrial sector in the Baranangsiang area, Bogor city, West Java during the Covid 19 pandemic.. The purpose of this study is to better understand how far this qualitative descriptive research uses the content method with 25 informants on the results of long distance interviews from representatives of MSME actors in the Baranangsiangsubdistrict,BogorCity,West Java. To better understand creative economic empowerment properly and optimally . This research is very useful and helps MSME entrepreneurship who will increase their productivity performance in the creative economy,especially the agriculture agribusiness industry sector.Improvement of MSME business performance through a program to strengthen MSME empowerment through a quality creative economic network in the agriculture sector of the agro business industry which is maximal and productive.Limitations of the study. Research limitation is the importance of implementing, understanding and practical implementation in implementing empowerment networks,especially for business unit services in the Baranangsiang area, Bogor City,West Java. The contribution of this research is to improve MSME empowerment services through the creative economy of the agricultural agribusiness sector in a strong and professional manner.The results of this study include empowering MSMEs through MSME performance productivity and optimizing the growth of MSME business service networks and MSME empowerment programs in an integrated creative economy